Factors Influencing Recovery From Pediatric Stroke Based on Discussions From a UK-Based Online Stroke Community: Qualitative Thematic Study - Charlotte Howdle; William James Alexander Wright; Jonathan Mant; Anna De Simoni (JMIR Publications, 2024)
BackgroundThe incidence of stroke in children is low, and pediatric stroke rehabilitation services are less developed than adult ones. Survivors of pediatric stroke have a long poststroke life expectancy and therefore have the potential to experience impairments from their stroke for many years. However, there are relatively few studies characterizing these impairments and what factors facilitate or counteract recovery. ObjectiveThis study aims to characterize the main barriers to and facilitators of recovery from pediatric stroke. A secondary aim was to explore whether these factors last into adulthood, whether they change, or if new factors impacting recovery emerge in adulthood. MethodsWe performed a qualitative thematic analysis based on posts from a population of participants from a UK-based online stroke community, active between 2004 and 2011. The analysis focused on users who talked about their experiences with pediatric stroke, as identified by a previous study. The posts were read by 3 authors, and factors influencing recovery from pediatric stroke were mapped into 4 areas: medical, physical, emotional, and social. Factors influencing recovery were divided into short-term and long-term factors. ResultsThere were 425 posts relating to 52 survivors of pediatric stroke. Some survivors of stroke posted for themselves, while others were talked about by a third party (mostly parents; 31/35, 89% mothers). In total, 79% (41/52) of survivors of stroke were aged ≤18 years and 21% (11/52) were aged >18 years at the time of posting. Medical factors included comorbidities as a barrier to recovery. Medical interventions, such as speech and language therapy and physiotherapy, were also deemed useful. Exercise, particularly swimming, was deemed a facilitator. Among physical factors, fatigue and chronic pain could persist decades after a stroke, with both reported as a barrier to feeling fully recovered. Tiredness could worsen existing stroke-related impairments. Other long-standing impairments were memory loss, confusion, and dizziness. Among emotional factors, fear and uncertainty were short-term barriers, while positivity was a major facilitator in both short- and long-term recovery. Anxiety, grief, and behavioral problems hindered recovery. The social barriers were loneliness, exclusion, and hidden disabilities not being acknowledged by third parties. A good support network and third-party support facilitated recovery. Educational services were important in reintegrating survivors into society. Participants reported that worrying about losing financial support, such as disability allowances, and difficulties in obtaining travel insurance and driving licenses impacted recovery. ConclusionsThe lived experience of survivors of pediatric stroke includes long-term hidden disabilities and barriers to rehabilitation. These are present in different settings, such as health care, schools, workplaces, and driving centers. Greater awareness of these issues by relevant professional groups may help ameliorate them.